2019
DOI: 10.1186/s40560-019-0383-3
|View full text |Cite
|
Sign up to set email alerts
|

Variations in infection sites and mortality rates among patients in intensive care units with severe sepsis and septic shock in Japan

Abstract: Background Accurate and early identification of infection sites might help to drive crucial decisions regarding the treatment of sepsis. We aimed to determine the clinical and etiological features of infection according to sites among patients with severe sepsis in Japan. Methods This secondary analysis of a multicenter, prospective cohort study included 59 intensive care units (ICU) and proceeded between January 2016 and March 2017. The study cohort comprised 1184 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
52
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 19 publications
10
52
2
1
Order By: Relevance
“…Our finding of reduced odds of short-term mortality among septic SLE hospitalizations admitted to the ICU who had urinary tract infections (UTI), as compared with those having an infection of the respiratory tract, is consistent with prior studies of sepsis in the general population [51,52]. The factors underlying the more favorable outcome among septic patients with UTI remain uncertain.…”
Section: Relationship To Previous Studiessupporting
confidence: 86%
“…Our finding of reduced odds of short-term mortality among septic SLE hospitalizations admitted to the ICU who had urinary tract infections (UTI), as compared with those having an infection of the respiratory tract, is consistent with prior studies of sepsis in the general population [51,52]. The factors underlying the more favorable outcome among septic patients with UTI remain uncertain.…”
Section: Relationship To Previous Studiessupporting
confidence: 86%
“…They had prolonged organ dysfunction and the worst 12-month survival with notably poor functional outcomes. Previous studies looking at the role site of infection in outcomes after sepsis principally focused on hospital mortality [12][13][14][15]33]. From these reports, it can be concluded that site of infection does have an independent effect on hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, innumerable trials of promising immune-modulating interventions have failed to reduce early mortality and the recent consensus is that heterogeneity played a major role in these dismal failures [8][9][10]. It has been shown that site of infection is an independent predictor of early mortality [11][12][13][14][15]. However, the epidemiology of sepsis has evolved.…”
Section: Introductionmentioning
confidence: 99%
“…Not only pulmonary but also severe soft tissue infection could be a novel risk modifier. However, these patients were more likely to be admitted to wards instead of ICUs, presumably because shock was less common [33]. By limiting our cohort to ICUs, we may have introduced some bias.…”
Section: Discussionmentioning
confidence: 99%